Chemotherapy-associated liver injury in colorectal cancer. (May 2020) - Gangi, Alexandra; Lu, Shelly C.
Patients with colorectal cancer (CRC) have benefited significantly from advances in multimodal treatment with significant improvements in long-term survival. More patients are currently being treated with surgical resection or ablation following neoadjuvant or adjuvant chemotherapy. However, several cytotoxic agents that are administered routinely have been linked to liver toxicities that impair liver function and regeneration. Recognition of chemotherapy-related liver toxicity emphasizes the importance of multidisciplinary planning to optimize care. This review aims to summarize current data on multimodal treatment concepts for CRC, provide an overview of liver damage caused by commonly administered chemotherapeutic agents, and evaluate currently suggested protective agents.